2021
DOI: 10.1007/s00221-021-06047-2
|View full text |Cite
|
Sign up to set email alerts
|

Auditory perception is influenced by the orientation of the trunk relative to a sound source

Abstract: The study investigated how hearing depends on the whole body, head and trunk orientation relative to a sound source. In normal hearing humans we examined auditory thresholds and their ability to recognize logatomes (bi-syllabic non-sense words) at different whole body, head and trunk rotation relative to a sound source. We found that auditory threshold was increased and logatome recognition was impaired when the body or the trunk were rotated 40° away from a sound source compared to when the body or the trunk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…They complement the previous findings by showing what happens in a less structured context. The bias identified in head-pointing tasks was shown to be a function of headon-trunk eccentricity (Makous and Middlebrooks, 1990;Lewald et al, 2000;Occhigrossi et al, 2021). Instead, in our task, the relative position between participant's seat and sound source is continuously updated (participants "sit" on the virtual arrow, which advances in the virtual space at fixed speed).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…They complement the previous findings by showing what happens in a less structured context. The bias identified in head-pointing tasks was shown to be a function of headon-trunk eccentricity (Makous and Middlebrooks, 1990;Lewald et al, 2000;Occhigrossi et al, 2021). Instead, in our task, the relative position between participant's seat and sound source is continuously updated (participants "sit" on the virtual arrow, which advances in the virtual space at fixed speed).…”
Section: Discussionmentioning
confidence: 83%
“…Data collected with forced coordination were compared to those collected with free coordination to evaluate the ability of early blind individuals and sighted controls to localize dynamic sounds by head-pointing while self-immobilizing their trunk on both kinematics and spatial performance standpoints. The distinction between central and lateral direction levels was maintained in the analysis to assess behavioral differences between frontal and eccentric targets, as previously found for auditory localization by head-pointing (Lewald et al, 2000;Occhigrossi et al, 2021). Results are reviewed separately for each measure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participant starts with their head and trunk aligned to the straight-ahead direction. We distinguished between central and lateral targets because previous research on auditory localization in the horizontal plane by head-pointing showed different spatial performance in eccentric stimuli between sighted and blind people (Lewald et al, 2000;Makous and Middlebrooks, 1990;Occhigrossi et al, 2021).…”
Section: Tasks Descriptionmentioning
confidence: 99%